Investigation of Leaf Surface Development in Strawberry (Fragaria × ananassa) under Differential Water Supply Conditions - Simon-Gáspár, Brigitta; Simon, Szabina; Tóth, Gellért Gergely; Szabó, Péter (GEORGIKON FOR AGRICULTURE, 2025)
Strawberry (Fragaria × ananassa) is undoubtedly one of the most popular berry crops both in Hungary and worldwide. It can be cultivated using several production methods, most commonly under open-field conditions. In open-field cultivation, water supply represents a critical factor, particularly in the context of climate change. The increasing unpredictability of precipitation threatens yield stability. In our experiment, the responses of three strawberry cultivars (Senga S, Honeoye and Kortes) were examined to determine how their leaf surface area and yield were affected by varying water supply levels. Four irrigation regimes were established: optimal irrigation, and 75%, 50% and 40% of the optimal irrigation volume. Leaf surface area exhibited a sensitive response to water deficit; in all cultivars, decreasing irrigation volumes resulted in a reduction of leaf surface area. Yield assessments indicated that even a 25% reduction in water supply caused a drastic yield decline, ranging from 56.1% to 70.6%. Overall, the results demonstrate that adequate water availability is essential for successful strawberry production and for achieving optimal yield levels in the cultivars included in this study.